2020
DOI: 10.1200/jco.2020.38.6_suppl.93
|View full text |Cite
|
Sign up to set email alerts
|

Oligopelvis-GETUG P07: A multicenter phase II trial of combined salvage radiotherapy and hormone therapy in oligorecurrent pelvic node relapses of prostate cancer.

Abstract: 93 Background: Oligorecurrent pelvic nodal relapse of prostatic cancer is a challenge for regional salvage treatments. We conducted OLIGOPELVIS – GETUG P07, a phase II trial of combined salvage radiotherapy and hormone therapy in oligorecurrent pelvic node relapses of prostate cancer (NCT02274779). Methods: OLIGOPELVIS–GETUG P07 was a prospective multi-center phase II trial investigating high-dose salvage pelvic irradiation with an additional dose to the fluorocholine-based positron-emission-tomography (FCH- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…analyzed patterns of nodal failure according to Morón et al. using 34 abdomino-pelvic stations ( 13 , 28 ). These circumstances can lead to possible misinterpretation of study results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…analyzed patterns of nodal failure according to Morón et al. using 34 abdomino-pelvic stations ( 13 , 28 ). These circumstances can lead to possible misinterpretation of study results.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal target volume design is also a pressing question in the context of nodal oligorecurrent prostate cancer, as there is a rising practice of treating nodal oligorecurrent prostate cancer with salvage lymph node dissection and/or radiotherapy ( 5 ). In retrospective case series and phase II trials, these metastasis-directed therapies have shown promising progression-free survival with limited toxicity ( 5 , 28 ). In case of radiotherapy for oligorecurrent nodal disease, current target volume concepts vary from involved node SBRT, involved site SBRT to involved field RT and elective whole pelvic RT without a clear standard having been established yet ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal target volume design is also a pressing question in the context of nodal oligorecurrent prostate cancer, as there is a rising practice of treating nodal oligorecurrent prostate cancer with salvage lymph node dissection and/or radiotherapy (5). In retrospective case series and phase II trials, these metastasisdirected therapies have shown promising progression-free survival with limited toxicity (5,28). In case of radiotherapy for oligorecurrent nodal disease, current target volume concepts vary from involved node SBRT, involved site SBRT to involved field RT and elective whole pelvic RT without a clear standard having been established yet (4).…”
Section: Months After Rtmentioning
confidence: 99%